The Antiproliferative and Apoptotic Effects of Capsaicin on an Oral Squamous Cancer Cell Line of Asian Origin, ORL-48 - Kamaruddin, Mohammad Firdaus; Hossain, Mohammad Zakir; Mohamed Alabsi, Aied; Bakri, Marina Mohd (MDPI, 2019)
Background and Objectives: The antitumor activities of capsaicin on various types of cancer cell lines have been reported but the effect of capsaicin on oral cancer, which is prevalent among Asians, are very limited. Thus, this study aimed to investigate the effects of capsaicin on ORL-48, an oral cancer cell line of Asian origin. Materials and Methods: Morphological changes of the ORL-48 cells treated with capsaicin were analyzed using fluorescence microscopy. The apoptotic-inducing activity of capsaicin was further confirmed by Annexin V-Fluorescein isothiocyanate/Propidium iodide (V-FITC/PI) staining using flow cytometry. In order to establish the pathway of apoptosis triggered by the compound on ORL-48 cells, caspase activity was determined and the mitochondrial pathway was verified by mitochondrial membrane potential (MMP) assay. Cell cycle analysis was also performed to identify the cell cycle phase of ORL-48 cells being inhibited by the capsaicin compound. Results: Fluorescence microscopy exhibited the presence of apoptotic features in capsaicin-treated ORL-48 cells. Apoptosis of capsaicin-treated ORL-48 cells revealed disruption of the mitochondrial-membrane potential, activation of caspase-3,-7 and-9 through an intrinsic apoptotic pathway and subsequently, apoptotic DNA fragmentation. The cell cycle arrest occurred in the G1-phase, confirming antiproliferative effect of capsaicin in a time-dependent manner. Conclusion: This study demonstrated that capsaicin is cytotoxic against ORL-48 cells and induces apoptosis in ORL-48 cells possibly through mitochondria mediated intrinsic pathway resulting in cell cycle arrest. © 2019 by the authors.